Proceedings of the 8th International Conference on Computer Recognition Systems CORES 2013 - Burduk, Robert.; Burduk, Robert.; Jackowski, Konrad.; Jackowski, Konrad.; Kurzynski, Marek.; Kurzynski, Marek.; Wozniak, Michał.; Wozniak, Michał.; Zolnierek, Andrzej.; Zolnierek, Andrzej. (Advances in Intelligent Systems and Computing, 2013)
The computer recognition systems are nowadays one of the most promising directions in artificial intelligence. This book is the most comprehensive study of this field. It contains a collection of 86 carefully selected articles contributed by experts of pattern recognition. It reports on current research with respect to both methodology and applications. In particular, it includes the following sections: Biometrics Data Stream Classification and Big Data Analytics  Features, learning, and classifiers Image processing and computer vision Medical applications Miscellaneous applications Pattern recognition and image processing in robotics  Speech and word recognition This book is a great reference tool for scientists who deal with the problems of designing computer pattern recognition systems. Its target readers can be the as well researchers as students of computer science, artificial intelligence or robotics.